Unveiling the amplified oxidase-mimetic activity of MnCoO nanosheets for the ultra-sensitive determination of the long-acting beta-adrenoceptor agonist indacaterol - Amal A. El-Masry; Heba Elmansi; Nahed El-Enany (Talanta Open)
The ability to determine indacaterol in different matrices is critical for the medication adherence assessment. In the current approach, we introduce a pioneering colorimetric detection approach for the sensitive quantitation of indacaterol using ultrathin MnCoO nanosheets with boosted oxidase-imitating properties. The nanosheets were synthesized under mild conditions through a one-step template-less simple hydrothermal process. These nanosheets demonstrated oxidase-imitating activity, enabling the change of (3,3′,5,5′-Tetramethylbenzidine ) TMB into blue-colored oxidized TMB without the need for water. Yet, the presence of indacaterol impeded this action, leading to the transformation of oxidized TMB back to colorless TMB and a subsequent reduction in blue color intensity is observed. The colorimetric reaction showed a linear correlation with indacaterol concentrations ranging from 6.0  325.0 ng/mL. This ultra sensitivity permitted reaching a detection limit down to 1.77 ng/mL. Different characterization and kinetic experiments were conducted to elucidate the underlying mechanism. Additionally, the effectiveness of the sensing platform was evaluated by measuring indacaterol levels in its pharmaceuticals. A green assessment for this approach was introduced. This well-established methodology highlights the potential of nanomaterial-based sensing technologies in pharmaceutical analysis, and related fields.